Highly efficient catalytic hydrogenation of nitrophenols by sewage sludge derived biochar. (1st August 2021) - Ren, Xiaoya; Tang, Lin; Wang, Jiajia; Almatrafi, Eydhah; Feng, Haopeng; Tang, Xiang; Yu, Jiangfang; Yang, Yang; Li, Xiaopei; Zhou, Chenyun; Zeng, Zhuotong; Zeng, Guangming
Abstract: Finding a low cost and effective alternative to noble metal based catalyst has long been concerned in wastewater treatment and organic transformation. This work developed a highly efficient sewage sludge-based catalyst via a simple one-step pyrolysis method, and for the first time, applied it in the catalytic reduction of nitrophenols. Due to the higher content of graphitic nitrogen, abundant defect sites and low electron transfer resistance, sewage sludge derived biochar obtained at 800 °C (SSBC-800) exhibits the best catalytic performance, with the reaction rate of 0.48 min −1 and turnover frequency for 4-nitrophenol calculated to be 1.25 × 10 −4 mmolmg −1 min −1, which is comparable to or even superior than some reported noble metal-based catalyst. Moreover, SSBC-800 showed good recyclability of 90% 4-nitrophenol removal within 8 min after 4 runs, and maintained high catalytic activity in reduction of other substituent nitrophenols, such as 2-nitrophenol (0.54 min −1 ), 3-nitrophenol (0.61 min −1 ) and 2, 4-dinitrophenol (0.18 min −1 ), and in real water samples, indicating its practical applicability. The electron paramagnetic resonance spectra and electrochemical characterization demonstrate that SSBC-800 accelerates the dissociation of BH4 − to form active hydrogen, which is the main species responsible for 4-nitrophenol reduction, while electron transfer reaction involving the surface bound hydride derived from the intimate contact between BH4 − and SSBC-800 plays an important role in this process. This research not only provides a novel valorization pathway for sewage sludge, but also sheds new light on further designing of carbon-based catalyst for nitrophenol reduction. Graphical abstract: Image, graphical abstract